Peran Sekretariat Badan Legislasi Dewan Perwakilan Rakyat Republik Indonesia Dalam Rangka Penyusunan Rancangan Undang-Undang di DPR RI Jakarta Periode 2009-2014 - Herda Prabadipta (Jurnal Administrasi Publik, 2014)
Abstract: The Role of Legislation Committee Secretariat The House of Representatives of Republic of Indonesia (DPR RI) In The Draft Law Preparation On DPR RI Jakarta 2009-2014. To understand the role of the Secretariat of the Legislative Committee, the researchers used a type of qualitative research methods with a descriptive approach. The focus raised is how the role of the Secretariat of Legislation in providing administrative support in the process of drafting the law draft, through the viewpoint of administrative management functions, which consist of: planning, organizing, actuating and controlling. Based on the research results, it can be seen that the overall administrative support provided by the Secretariat of Legislation Committee for the members of the Legislative Committee. However, adding performance results of Legislation required cooperation from both, the Secretariat of Legislation Committee and the Legislation Committee Board itself. Keywords: Roles, secretariat, policy, legislation, House of Representatives Abstrak: Peran Sekretariat Badan Legislasi Dewan Perwakilan Rakyat Republik Indonesia Dalam Rangka Penyusunan Rancangan Undang-Undang Di DPR RI Jakarta Periode 2009-2014. Dalam memahami peran Sekretariat Badan Legislasi tersebut, peneliti menggunakan jenis metode penelitian kualitatif dengan pendekatan deskriptif. Fokus yang diangkat adalah bagaimana peran Sekretariat Badan Legislasi dalam memberikan dukungan administratif dalam proses penyusunan RUU, melalui sudut pandang fungsi manajemen administrasi, yaitu perencanaan, pengorganisasian, pelaksanaan dan pengawasan. Berdasarkan hasil penelitian, dapat diketahui bahwa secara keseluruhan dukungan administratif anggota Badan Legislasi diberikan oleh Sekretariat Badan Legislasi. Bagaimanapun, dibutuhkan kerjasama dari kedua pihak untuk meningkatkan hasil kinerja legislasi. Kata Kunci: Peran, sekretariat, kebijakan, legislasi, DPR RI